Socialization of Umkm Activities to Entrepreneurship Students with Halal Local Food Processed Products - Yunarni, Baiq Reinelda Tri; K.Tobing, Diana Sulianti; Nuraini, Nuraini (Abdi Masyarakat, 2025)
This study aims to determine the effectiveness of MSME socialization activities in increasing students' understanding and interest in entrepreneurship towards the development of local halal processed food products. The main focus of this activity is to encourage students to actively participate in the development of local wisdom-based businesses that are in accordance with sharia principles, as well as creating products that are competitive in the halal market. The methods used in this study are quantitative and qualitative methods through a descriptive approach, with data collection techniques in the form of observations, questionnaires, and interviews with student participants and directly involved in entrepreneurship with the Community Service team.The results of the study showed that 85% of students experienced an increase in understanding of the concept of sharia MSMEs and the importance of halal products after participating in the socialization activities. As many as 70% of participants stated that they were interested in starting a business based on local halal food products, and 75% of them had produced business ideas that were ready to be developed further. In addition, this activity also succeeded in encouraging collaboration between students in the form of small business groups based on local processed food. Thus, MSME socialization has proven effective in fostering a halal entrepreneurial spirit among students and strengthening sustainable local economic potential.